Field reports form for submitting seasonal observations of Iowa birds, Ed Thelen, Spring 1994 - Thelen, Edet al (1994)
An annotated list of birds sighted by Ed Thelen and two others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed